High-frequency spontaneous electromagnetic noise of lithosphere and tomographic systems - Shuman, V. (Geofizicheskiy Zhurnal, 2014)
The questions on the problem of restoration of three-dimensional images of physical properties and structural features of geo-medium applying the methods of transmission, diffraction and emission tomography that use seismic and electromagnetic waves, their informative abilities, resolvability and precision of objects localization have been examined in the paper. The approaches are accentuated, which are based on the ideas and principles of non-linear dynamics to solve tomographic problems, abilities to adapt and transfer the ideas of seismic tomography to electromagnetic systems, in particular, tomography of spontaneous electromagnetic emission of kilohertz range, which is generated in lithosphere of the Earth. Specific examination is conducted on the base of extended ideas on geo-medium as well as new versions of mechanisms of its generation and distribution based on auto-wave character of processes in geo-medium. Basic properties of wave and auto-wave processes are being compared. Controversial problems of theory are noticed, absence of universal character of classical concepts, in particular, in the case when appliance used weighs upon adequacy of consideration. Possibilities and some results of validation of experimental method are discussed.